Red Listing plants under full national responsibility: Extinction risk and threats in the vascular flora endemic to Italy. (August 2018) - Orsenigo, Simone; Montagnani, Chiara; Fenu, Giuseppe; Gargano, Domenico; Peruzzi, Lorenzo; Abeli, Thomas; Alessandrini, Alessandro; Bacchetta, Gianluigi; Bartolucci, Fabrizio; Bovio, Maurizio; Brullo, Cristian; Brullo, Salvatore; et al.
Abstract: Taxa endemic to a country are key elements for setting national conservation priorities and for driving conservation strategies, since their persistence is entirely dependent on national policy. We applied the IUCN Red List categories to all Italian endemic vascular plants (1340 taxa) to assess their current risk of extinction and to highlight their major threats. Our results revealed that six taxa are already extinct and that 22.4% (300 taxa) are threatened with extinction, while 18.4% (247; especially belonging to apomictic groups) have been categorized as Data Deficient. Italian endemic vascular plants are primarily threatened by natural habitat modification due to agriculture, residential and tourism development. Taxa occurring in coastal areas and lowlands, where anthropogenic impacts and habitat destruction are concentrated, display the greatest population decline and extinction. The national network of protected areas could be considered effective in protecting endemic-rich areas (ERAs) and endemic taxa, but ineffective in protecting narrow endemic-rich areas (NERAs), accordingly changes to the existing network may increase the effectiveness of protection. For the first time in the Mediterranean Basin biodiversity hotspot, we present a comprehensive extinction assessment for endemic plants under the full responsibility of a single country. This would provide an important step towards the prioritization and conservation of threatened endemic flora at Italian, European, and Mediterranean level. A successful conservation strategy of the Italian endemic vascular flora should implement the protected area system, solve some taxonomical criticism in poorly known genera, and should rely on monitoring threatened species, and on developing species-specific action plans. Highlights: The extinction risk of 1340 vascular plants narrowly endemic to Italy is assessed. The first national assessment of the whole endemic flora in the Mediterranean Basin. Six taxa are extinct and 300 taxa have been assigned to a threatened risk category. Natural system modification, tourism and agriculture are the major threats. Improvement of knowledge, population trends and conservation actions are needed.